2020
DOI: 10.1108/bfj-07-2020-0599
|View full text |Cite
|
Sign up to set email alerts
|

What motivates consumers to purchase organic food in an emerging market? An empirical study from Saudi Arabia

Abstract: PurposeThis study aims to investigate the impact of perceived values (hedonic and utilitarian), trust and subjective norms on consumers' purchasing intentions of organic food in Saudi Arabia; it also explores the moderating influence of availability on the relationship between the intentions of consumers and their actual purchasing behaviour.Design/methodology/approachA survey with 236 consumers of organic food in Saudi Arabia was carried out. The convergent and discriminant validity of latent variables was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 82 publications
0
34
1
Order By: Relevance
“…Subjective norm was non-significantly related to purchase intention. This finding is contrary to previous research by Chung et al (2012), Mohammed (2020) and Shah Alam and Mohamed Sayuti (2011), which found that subjective norm is a significant predictor in behavioural decisions, especially in Asian culture as opposed to individualistic cultures in western countries. They concluded that in collectivistic culture such as Asian countries, people tend to strive for in-group rather than personal goals.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Subjective norm was non-significantly related to purchase intention. This finding is contrary to previous research by Chung et al (2012), Mohammed (2020) and Shah Alam and Mohamed Sayuti (2011), which found that subjective norm is a significant predictor in behavioural decisions, especially in Asian culture as opposed to individualistic cultures in western countries. They concluded that in collectivistic culture such as Asian countries, people tend to strive for in-group rather than personal goals.…”
Section: Discussioncontrasting
confidence: 99%
“…TPB has been applied widely and successfully in many studies as a theoretical framework from which to examine the purchase intention in halal food consumption (Amalia et al, 2020;Lim at al., 2020;Marmaya at al., 2019), organic food consumption (James et al, 2019;Mohammed, 2020;Teng & Wang, 2015), functional food consumption (Xin & Seo, 2019), genetically modified food consumption (Rabbanee et al, 2020;Zheng et al, 2017;Zhu et al, 2018), green food consumption (Amin & Tarun, 2020), ethnic food consumption (Ahmad et al, 2019) and counterfeit products (Fernandes, 2013). Hence, the TPB model is deemed suitable as the theoretical foundation for this research to understand honey buyers' purchase intention.…”
Section: Theoretical Framework -Theory In Support Of Intention To Purchasementioning
confidence: 99%
“…Some studies believed that consumer perceived values play important roles in promoting the purchase of organic food (Suki and Suki, 2015a,b,c;Suki, 2016;Akbar et al, 2019;Kushwah et al, 2019a;Shamsi et al, 2020). In particular, health value, functional value and environmental value were identified as important factors in predicting organic purchasing behavior (Mohammed, 2020). Chekima et al (2017) found that consumers' attitudes toward organic food can play a positive role in organic consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that perceived values (utilitarian and hedonic) influence consumer willingness to buy organic foods [ 39 , 40 ]. It is the perceived value of a product from the multisensory and emotive aspects.…”
Section: Literature Reviewmentioning
confidence: 99%